EFFECT OF POWERPOINT PRESENTATION ON ACHIEVEMENT IN ENGLISH OF 9TH GRADE STUDENTS - Dr Rohtash (Innovative Research Thoughts, 2017)
Present paper is entitled Effect of PowerPoint presentation on achievement in English of 9th grade students. The purpose of the study was to understand the impact of PPT on achievement in English of 9th grade students. A sample of 60 students was selected by simple random sampling technique from different HBSE schools of Assandh. The study revealed that there is significant difference between the students taught through PowerPoint Presentation and students taught through Conventional method.